Neuroprotective potential of Marsilea quadrifolia Linn against monosodium glutamate-induced excitotoxicity in rats - Subramanian, Arunkumar; Tamilanban, T.; Sekar, Mahendran; Begum, M. Yasmin; Atiya, Akhtar; Ramachawolran, Gobinath; Wong, Ling Shing; Subramaniyan, Vetriselvan; Gan, Siew Hua; Mat Rani, Nur Najihah Izzati; Wu, Yuan Seng; Chinni, Suresh V.; et al. (Frontiers in Pharmacology, 2023)
Excitotoxicity is a condition in which neurons are damaged/injured by the over-activation of glutamate receptors. Excitotoxins play a crucial part in the progression of several neurological diseases. Marsilea quadrifolia Linn (M. quadrifolia) is a very popular aquatic medicinal plant that has been utilised for a variety of therapeutic benefits since ancient times. Its chemical composition is diverse and includes phenolic compounds, tannins, saponins, flavonoids, steroids, terpenoids, alkaloids, carbohydrates and several others that possess antioxidant properties. The objective of the present study was to investigate the neuroprotective potential of M. quadrifolia against monosodium glutamate (MSG)-induced excitotoxicity in rats. For this purpose, a high-performance thin-layer chromatography (HPTLC) analysis of chloroform extract of M. quadrifolia (CEMQ) was conducted to identify the major constituents. Further, the in-silico docking analysis was carried out on selected ligands. To confirm CEMQ's neuroprotective effects, the locomotor activity, non-spatial memory, and learning were assessed. The present study confirmed that CMEQ contains quercetin and its derivatives in large. The in-silico findings indicated that quercetin has a better binding affinity (-7.9 kcal/mol) towards the protein target 5EWJ. Animals treated with MSG had 1) a greater reduction in the locomotor score and impairment in memory and learning 2) a greater increase in the blood levels of calcium and sodium and 3) neuronal disorganization, along with cerebral edema and neuronal degeneration in the brain tissues as compared to normal control animals. The changes were however, significantly improved in animals which received standard drug memantine (20 mg/kg) and CEMQ (200 and 400 mg/kg) as compared to the negative control. It is plausible that the changes seen with CEMQ may be attributed to the N-methyl-D-aspartate (NMDA) antagonistic properties. Overall, this study indicated that M. quadrifolia ameliorated MSGinduced neurotoxicity. Future investigations are required to explore the neuroprotective mechanism of M. quadrifolia and its active constituents, which will provide exciting insights in the therapeutic management of neurological disorders.